Pentingnya Kepemimpinan Digital dan Motivasi Terhadap Kinerja Karyawan - Feti Fatonah; Anistazkia Miftahul Jannah; Erlina Dwi Santika. Sn.; Luthfi Musthofa; Wahyu Wira Bhaskara (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2024)
This study aims to investigate the impact of digital leadership on organizational performance, focusing on its role in enhancing effectiveness in the era of globalization. The research adopts a comprehensive literature review approach, analyzing various studies to understand the multifaceted aspects of digital leadership and its implications for organizational performance. The findings reveal that digital leadership goes beyond technological adoption, encompassing cultural and structural transformations within organizations. The study acknowledges the limitations inherent in a literature review approach, such as potential bias in the selected sources. In conclusion, the practical implications of this study advocate for a balanced and strategic approach to digital leadership, acknowledging the interconnectedness of technology and human factors. This research contributes to the understanding of digital leadership by emphasizing its holistic nature, incorporating both technological and human elements. The study highlights the strategic necessity of digital leadership in ensuring organizational relevance and competitiveness in the evolving digital landscape